A small hypoxia signature predicted pCR response to bevacizumab in the neoadjuvant GeparQuinto breast cancer trial - Karn, Thomas; Meissner, Tobias; Weber, Karsten E.; Solbach, Christine; Denkert, Carsten; Engels, Knut; Fasching, Peter A.; Sinn, Bruno V.; Schrader, Iris; Budczies, Jan; Marmé, Frederik; Müller, Volkmar; et al. (Clinical cancer research, 2020)
Purpose: In breast cancer, bevacizumab increased pCR rate but not long-term survival and no predictive markers are available to identify patients with long-term benefit from the drug. - Experimental Design: We profiled 289 pretherapeutic formalin-fixed, paraffin-embedded (FFPE) biopsies of HER2-negative patients from the GeparQuinto trial of neoadjuvant chemotherapy ± bevacizumab by exome-capture RNA-sequencing (RNA-seq). In a prospectively planned study, we tested molecular signatures for response prediction. IHC validation was performed using tissue microarrays. - Results: We found strong agreement of molecular and pathologic parameters as hormone receptors, grading, and lymphocyte infiltration in 221 high-quality samples. Response rates (49.3% pCR overall) were higher in basal-like (68.9%) and HER2-enriched (45.5%) than in luminal B (35.7%), luminal A (17.9%), and normal-like (20.0%) subtypes. T-cell (OR = 1.60; 95% confidence interval, 1.21-2.12; P = 0.001), proliferation (OR = 2.88; 95% CI, 2.00-4.15; P < 0.001), and hypoxia signatures (OR = 1.92; 95% CI, 1.41-2.60; P < 0.001) significantly predicted pCR in univariate analysis. In a prespecified multivariate logistic regression, a small hypoxia signature predicted pCR (OR = 2.40; 95% CI, 1.28-4.51; P = 0.006) with a significant interaction with bevacizumab treatment (P = 0.020). IHC validation using NDRG1 as marker revealed highly heterogenous expression within tissue leading to profound loss of sensitivity in TMA analysis, still a significant predictive value for pCR was detected (P = 0.025). - Conclusions: Exome-capture RNA-seq characterizes small FFPE core biopsies by reliably detecting factors as for example ER status, grade, and tumor-infiltrating lymphocytes levels. Beside molecular subtypes and immune signatures, a small hypoxia signature predicted pCR to bevacizumab, which could be validated by IHC. The signature can have important applications for bevacizumab treatment in different cancer types and might also have a role for novel combination therapies of bevacizumab with immune checkpoint inhibition.